A boron-exposed TiB3 monolayer with a lower electrostatic-potential surface as a higher-performance anode material for Li-ion and Na-ion batteries. Issue 39 (1st October 2020) - Li, Rong; Wang, Yatong; Xu, Li-Chun; Shen, Jiale; Zhao, Wenyang; Yang, Zhi; Liu, Ruiping; Shao, Jian-Li; Guo, Chunli; Li, Xiuyan
Abstract : The lack of high-performance anode materials has become a major obstacle to the development of Li- and Na-ion batteries. Abstract : The lack of high-performance anode materials has become a major obstacle to the development of Li- and Na-ion batteries. Recently, 2D transition metal borides ( e.g. MBenes) have attracted much attention due to their excellent stability and electrical conductivity. Unfortunately, most of the reported MBene phases typically have an intrinsic metal-rich structure with metal atoms exposed on the surface, which harmfully affect the adsorption of Li/Na atoms. Here, through crystal structure prediction combined with the first-principles density functional theory, a novel TiB3 MBene has been determined by altering the proportion of non-metallic element boron to wrap metal atoms and weaken nearest-neighbor electrostatic repulsion. Electrostatic potential analysis visually shows a surface with low potential on the TiB3 monolayer implying high adsorption capacity, and also can be used to quickly screen out the Li/Na adsorption sites. Accurate half-cell battery simulation confirmably shows that the TiB3 monolayer possesses a theoretical specific capacity of 1335.04 and 667.52 mA h g −1 for Li and Na, respectively. The TiB3 monolayer can remain metallic after adsorbing Li/Na atoms, which ensures good conductivity during battery cycling. The ultra-low barrier energy (only 38 meV for Li) and suitable open-circuit voltage indicate excellent charging and discharging capabilities. These results suggest that the TiB3 monolayer could be a promising anode material for Li- and Na-ion batteries, and provide a simple design principle for exposing non-metallic atoms on the surface.